THE EXISTENCE OF CITIZENSHIP EDUCATION IN ELEMENTARY SCHOOLS IN STRENGTHENING NATIONAL CHARACTER - Harahap, Syawal Fitrah (FORUM PAEDAGOGIK, 2025)
Civics Education (PKn) in elementary schools is understood as the initial foundation for the formation of national character and social morals in children. The relevance of this study arises from the need to review the position of PKn in the Independent Curriculum, especially since the implementation of P5, which emphasizes strengthening the Pancasila-based student profile. This research explores and summarizes 23 scientific publications from various reputable journals to examine how PKn works in building democratic awareness, tolerance, and national identity in the younger generation. Through qualitative meta-analysis, we found a shift in the orientation of PKn, from being normative to being more reflective and experience-based. The values of Pancasila, the use of Problem-Based Learning (PBL), multicultural learning strategies, and the use of digital media appear to provide space for the growth of cooperation, empathy, and a sense of nationalism in the classroom. These changes demonstrate that PKn not only introduces the concept of the state but also brings it to life in students' daily attitudes and behaviors. The main conclusion emphasizes that the sustainability of PKn depends on the ability to integrate moral values with digital media, participatory learning, and the social context of the school. With this orientation, Civics has strong potential to prepare young citizens who are resilient, ethical, and adhere to the values of Pancasila amidst the dynamics of modern education.